Development Of Ground Response Curves For Longwall Tailgate Support Design - T. M. Barczak (The National Institute for Occupational Safety and Health (NIOSH))
Longwall tailgates in coal mines are often subject to severe mining induced loading and deformation. Innovative tailgate supports have been developed over the years to provide safe and economical access and a ventilation pathway at the tailgate. The support capacity and yield capabilities of the supports need to be matched to the loading imposed by the surrounding rock mass. The ground response curve can be used to represent the rock mass response to mining and its effect on support systems. The FLAC finite difference code was used to supplement field results by simulating a longwall tailgate and the associated ground response. The ground response curve is developed by modeling tailgate excavations with different internal support pressures and recording the resulting convergence. Ground response curves are developed for two typical longwalls operating in the Pittsburgh seam with weak and strong immediate roof. An additional model is presented in which the effect of weak overburden strata is simulated. The ground response is shown to be significantly affected by the strength of the immediate roof as well as the main roof. The importance of yield capacity of standing support is demonstrated. Gob height and compaction are found to affect the amount of convergence in the tailgate. The potential exists to develop site specific tailgate design curves by combining model results with field observations.